2016
DOI: 10.1007/s00464-016-5036-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ERCP for management of cholecystocholedocholithiasis

Abstract: IOERCP during LC is a safe and effective option for management of CCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…This was in contrary to 12% of studied patients in the study carried out by Stanley et al 11 In the study by Ding et al, the authors reported that LCBDE+LC stones had a lower recurrence rate. 10,11 As regard our series, the success rates of laparoscopic CBD exploration and ERCP for clearance of CBD were similar (Group A 96% vs. Group B 97.3%).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This was in contrary to 12% of studied patients in the study carried out by Stanley et al 11 In the study by Ding et al, the authors reported that LCBDE+LC stones had a lower recurrence rate. 10,11 As regard our series, the success rates of laparoscopic CBD exploration and ERCP for clearance of CBD were similar (Group A 96% vs. Group B 97.3%).…”
Section: Discussionsupporting
confidence: 52%
“…A study conducted by Elgeidie et al showed that pre-ERCP+LC was associated with a higher success rate of CBD stone clearance. 10 There was only one case suffered from retained common bile duct stones among patients belonged group A (4.5%). This was in contrary to 12% of studied patients in the study carried out by Stanley et al 11 In the study by Ding et al, the authors reported that LCBDE+LC stones had a lower recurrence rate.…”
Section: Discussionmentioning
confidence: 86%
“…Technical factors such as manipulation of and injection of contrast into the pancreatic duct, biliary balloon sphincter dilation and cannulation attempts lasting > 5 min, also increase the risk [33,35,36]. Intraoperative rendezvous ERCP is an effective and safe method to treat CBDS found at cholecystectomy and concomitant cholangiography [7][8][9][10][11][12][13][14]. The operative technique of laparo-endoscopic rendezvous is straight-forward and suitable for almost all patients with CBDS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years intraoperative rendezvous endoscopic retrograde cholangiopancreaticography (ERCP) has been established as an alternative method to treat common bile and Other Interventional Techniques * Eva-Lena Syrén eva.lena.syren@akademiska.se duct stones discovered during laparoscopic cholecystectomy. This laparo-endoscopic rendezvous (LERV) technique was first described in 1993 by Deslandres et al [6] and has been shown to have a high rate of CBD stone clearance and a lower complication rate, particularly post-ERCP pancreatitis, compared to conventional ERCP [7][8][9][10][11][12][13][14][15]. This may be due to the facilitated access to the common bile duct with less manipulation and trauma to the papilla Vateri.…”
mentioning
confidence: 99%
“…For patients with both cholecystolithiasis and choledocholithiasis, ERCP followed by LC or LC followed by ERCP has been the common treatment in recent years [13][14][15]. However, this therapy is also associated with some drawbacks, such as long duration of the procedures (because there are two procedures), prolonged hospital stay, and considerable cost [6,14,16].…”
Section: Discussionmentioning
confidence: 99%